Rice Yield Gaps in India and Strategies to Narrow the Gaps - Bhanusree, D.; Nirmala, B.; Rathod, Santosha; Sriramulu, T.; Jyotsna, B.; Muthuraman, P. (Chronicle of Bioresource Management, 2023)
Rice is the staple food crop of India. The productivity of rice in India is comparatively low (2.4 tha-1)and ought to be raised to ensure sufficient production to meet the needs of the growing population. There are few ‘yield gaps in rice and closing the same could improve the productivity and efficiency of rice production. The paper discusses various concepts related to the yield gaps in rice and strategies to address such gaps. It is suggested that there should be institutional and policy support to farmers which is crucial for ensuring agricultural input supplies, farm credit and minimum support price in a holistic approach for a sustainable increase in rice production and for narrowing the yield gaps in rice.